Minding the Gap: Leveraging Mindfulness to Inform Cue Exposure Treatment for Substance Use Disorders - Vinci, Christine; Sawyer, Leslie; Yang, Min-Jeong (Frontiers in Psychology, 2021)
Despite extinction-based processes demonstrating efficacy in the animal extinction and human anxiety literatures, extinction for substance use disorders (SUD) has shown poor efficacy (i.e., cue exposure treatment [CET]). Reasons for this lack of success include common threats to extinction, such as renewal and reinstatement. In recent decades, research on mindfulness for SUD has flourished, and a key aspect of these mindfulness-based interventions includes teaching individuals to stay present with whatever experience they have, even if unpleasant, without trying to change/escape/avoid it. Similarly, CET teaches individuals to not escape/avoid conditioned responses (e.g., craving) by engaging in drug use behavior. This paper discusses how mindfulness-based research and practices could positively influence CET through future research (e.g., Could mindfulness practice attenuate renewal? Might mindfulness training + CET enhance the ability to extinguish the most salient or motivational cues?), with the long-term goal of improving SUD treatment.